Internet Begging: A Comparative Study between Jordanian and UAE Law and International Law - Al-khawaldeh, Moayd Husni Ahmad; Hammadi , Kazem Khalifa; Khawaldeh, Rafat Ibrahim Radwan (Journal of Ecohumanism, 2024)
The aim of the study is to show the extent of the criminal liability of perpetrators of Internet begging who solicit others’ sympathy on social media with the aim of obtaining financial compensation, which is through electronic transfers through various electronic means of payment. This requires a national and international legal action to curb this crime because it is on the rise. This study followed the descriptive, analytical and comparative approach. The descriptive approach is through the study of national laws in the Hashemite Kingdom of Jordan, laws in the United Arab Emirates and relevant international laws. The analytical approach is through the analysis of those previous laws. The comparative approach is through the comparison between the previous laws and the demonstration of strengths and weaknesses in each law. The study found that the UAE legislator was better than the Jordanian legislator when explicitly providing the crime of Internet begging in the Cybercrime Act because this shows the importance of the crime and illustrates its devastating effects on society, but the Jordanian legislator refers this crime to the Jordanian Penal Code, and the perpetrator is punished with a penalty that is more severe than provided by the UAE Cybercrime Act. With regard to the recommendations, I wish the Jordanian legislator to explicitly provide the crime of Internet begging and the proposed provision as follows: "anyone who commits the crime of Internet begging using the means of Information Technology in any form or means shall be punished with imprisonment for a period of not less than three months or a fine of not less than five thousand dinars and not more than ten thousand dinars or both of these penalties."